MECHANISMS OF STATE STIMULATION OF ENTREPRENEURIAL ACTIVITY: INTERNATIONAL EXPERIENCE AND PROSPECTS FOR IMPLEMENTATION IN UKRAINE - Kosmirak, Andrii (Public Management and Policy, 2025)
This piece examines the critical matter of how states can best support entrepreneurial efforts, drawing from global practices and considering their potential use in Ukraine. The importance of this research stems from the necessity to create fresh strategies that encourage entrepreneurship. The goal is to adjust to present economic realities and to enhance competitiveness on a global scale. Key issues that have been noticed include inadequate state backing for entrepreneurs, insufficient financial incentives, and the obstacles posed by military and political circumstances. The objective is to enhance Ukrainian state policy supporting entrepreneurship by implementing efficient and successful incentive systems, drawing from global best practices. The research seeks to improve Ukraine’s entrepreneurship policy, aimed at minimizing obstacles to business growth, boosting innovation, and fostering economic advancement. The study employs comparative analysis, forecasting, and modeling. The analysis of current academic literature reveals that Ukrainian researchers scrutinize entrepreneurial legislation and identify trends in stimulating entrepreneurial activity, considering insights from developed nations. This paper outlines the significance of entrepreneurship for the economy in broad terms. It clarifies the concept and core of how the state encourages entrepreneurs. By analyzing the methods used by Sweden, Germany, the United States, Singapore, China, and the United Kingdom, this study pinpoints successful strategies for government support of entrepreneurial activities. Some of these methods could be adopted in contemporary Ukraine. The article assesses Ukraine's current tools to support its entrepreneurs and compares these with global practices. Finally, it suggests a model for creating a system of state-led support for entrepreneurship. This model enables improved interaction between governmental bodies and business owners, thus boosting the effectiveness of program execution. It permits adjustments to public policy and informed decision-making based on entrepreneur feedback, simplifying the process of overseeing and assessing public policy outcomes, while aiding in timely adjustments. Recommendations for bolstering state support for entrepreneurship within Ukraine are offered. The conclusions highlight that integrating international best practices in Ukraine can significantly enhance the business environment, fostering job creation, attracting investment, and encouraging innovation.